Comparative Preclinical Evaluation of the Safety, Antifungal Activity, and Pharmacokinetics of Sertaconazole Products for External Use - V. M. Kosman; M. V. Karlina; V. A. Vavilova; K. E. Borovkova; K. L. Kryshen; N. V. Marchenko; S. A. Kopatko; I. V. Sychkova; D. R. Kargopoltseva; M. N. Makarova; V. G. Makarov (Безопасность и риск фармакотерапии)
SCIENTIFIC RELEVANCE. The high prevalence of fungal skin infections motivates expanding the range of sertaconazole products for external use.AIM. The study was a preclinical comparison of the safety, antifungal activity, and pharmacokinetics of Sertaverin® 2% medicated shampoo (VERTEX JSC, Russia) with those of Sertamicol® 2% solution for external use (Glenmark Pharmaceuticals Ltd, India) and Nizoral® 2% shampoo (Janssen Pharmaceuticals N.V., Belgium) approved in the Russian Federation.MATERIALS AND METHODS. In the toxicity study, the medicinal products were applied to the skin of male and female outbred rats at doses of 0.5 or 1.5 mL/animal for 28 days. The authors evaluated the pharmacokinetics of two sertaconazole formulations (shampoo and solution) following a single administration to adult male rats at the same dose. Nizoral® was not used in the pharmacokinetics study because it contains a different active substance, ketoconazole. The minimum inhibitory concentration (MIC) was determined using the serial microdilution method in a wide range of concentrations.RESULTS. The medicinal products did not exhibit any significant toxic effects in laboratory animals after 28 days of repeated dermal application. Plasma sertaconazole concentrations were negligible. Sertaconazole was intensively distributed in the liver, which is a highly vascularised organ, and in the target organ (skin at the site of application). The relative bioavailability of sertaconazole from the shampoo relative to that from the solution for external use was approximately 30% in liver tissues and approximately 363% in skin tissues at the application site. Sertaverin® was comparable to sertaconazole in the active substance form in terms of inhibiting the growth of Malassezia furfur strains. The MICs calculated on the active substance basis were ≤16–64 μg/mL.CONCLUSIONS. With its synergistic dual mechanism of action, broad-spectrum antifungal activity, lipophilic properties, and low systemic absorption, Sertaverin® may provide a more effective and safe alternative to marketed medicinal products for scalp diseases.